Dynamic web portal to prevent f06.4 morbidity in times of Covid-19 pandemic (Ciencias de la Ingeniería y Aplicadas, 2022)
A pandemic is being experienced by the COVID19 virus that is affecting the lifestyle of most people, one of the most common recommendations of the authorities is to stay at home and avoid meetings with friends or family, but it is known that the human being by nature is a sociable being, so this has caused a growth in stress and anxiety in people harming mental health, quality of sleep and physical health causing problems in the quality of life of the individual and vulnerability towards the virus, with the development of the dynamic web portal seeks to prevent the morbidity of mental illnesses through podcast content, relaxation therapies through controlled breathing, positive news and a record of emotional state, the results obtained was a decrease in stress in a short term by the participants who collaborated in the study.
Keywords: Coronavirus; Stress; Web portal